Gender-Based Wage Gap in Thailand - Senkrua, Akkaya (Journal of Business, Innovation and Sustainability (JBIS), 2023)
Gender-based wage inequality is prevalent in countries around the globe, and Thailand is no stranger to gender wage discrimination. Specifically, this study is documentary research on pay differentials to investigate the factors contributing to the gender-based wage gap in Thailand by using wage decomposition methods. The findings indicate that the gender pay gap in the country has declined due to higher educational attainment of female workers. The male-female wage differential however remains despite the convergence in individual characteristics and endowments of male and female workers. The study also reveals that gender discrimination contributes to the persistent wage differential.